ANALISIS GAYA KEPEMIMPINAN DAN KOMPENSASI TERHADAP DISIPLIN KERJA PADA PT. RIZKA TAMA LINE BANDAR LAMPUNG - F a h r i z i - (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2014)
PT. Rizka Tama Line is a national shipping company which is engaged in ship agency.Problems encountered by the company is whether leadership style and compensation together givea positive and significant effect on the discipline of employees at PT. Rizka Tama Line BandarLampung.Based on the discussion, it can be concluded that the application of leadership styles atPT. Rizka Tama Line Bandar Lampung is good. It can be seen from the respondents answers whochose good as many as 21 people (91.30 %) and basic leadership styles applied is participation(91.30 %). The discipline of employees at PT. Rizka Tama Line Bandar Lampung is in the highcategory (good). It can be seen from 15 respondents answers (71 % ) of the 21 respondents.